Fair Trade in Sustainable Development. The Potential for Fair Trade Market Growth in Poland - Grażyna Śmigielska; Anna Dąbrowska; Małgorzata Radziukiewicz (Amfiteatru Economic Journal, 2015)
The paper presents the concept of Fair Trade, which is considered an alternative to conventional trade, and becomes increasingly popular in the Western countries. In addition, some results of empirical research, conveyed in Poland and aimed at diagnosis and assessment of Fairtrade products market, are provided. Fair trade is analysed not only in the broad theoretical context which shows its contribution to sustainable development and relation to corporate social responsibility, but also in the framework of supply chains management. The benefits from the Fairtrade label, including transaction costs reduction are indicated. The assumption is that to achieve them, consumer acceptance of the idea and willingness to buy Fairtrade products are necessary. The empirical research was focused on answering the question whether a market niche for Fairtrade goods exists in Poland and how to develop it by the means of communication tools. The market niche, although very small, has been identified and described. It is apparent that, in order to develop it, a public policy, aimed at raising the awareness of Fair Trade idea, is necessary as well as marketing activities like social marketing Internet campaigns and better and more prominently products display.
Keywords: F13; O15; M14; 330; Fair Trade; Fairtrade; sustainable development; corporate social responsibility; consumer attitude